(untitled) (Economic and Political Thought, 2015)
The article discusses the issue of development of small and medium-sized businesses in Poland from the perspective of evolutionary economics. The evolution of the SMBs sector and the development of its present shape in Poland started in the 1980s. At the same time (in the early 80s), evolutionary economics placed hopes on the creation of alternative theory in relation to the neoclassical approach. Eventually, the sector went through various stages of evolution, which authors defined and specified differently. Diversity was nothing bad in this area, just the opposite – it made it possible to work out many mutually supplementing theses and views on the issue from a broad perspective. However, in the author’s opinion, it is necessary to take into account the sixth stage of the sector’s evolution (five stages are usually discussed in literature), which would reflect the development state of the sector’s population after the completed process of assistance of the European Union.